OPTIMIZATION OF THE PROBABILISTIC ALGORITHM FOR RESOLVING AIRSPACE CONFLICTS - Gabriela STROE; Mihaela-Luminita COSTEA; Augustin SEMENESCU (Fiabilitate şi Durabilitate)
n this paper, an algorithm for automatic conflict resolution in real airspace was proposed, based on an original algorithm, explained in extenso in the paper. In this proposed new form, the algorithm takes into account the previously detected problems and proposes to solve all these problems that inevitably appeared in the process of scientific research.